Antioxidant Activity of Andrographolide from Andrographis paniculata leaf and Its Extraction Optimization by using Accelerated Solvent Extraction: Antioxidant Activity of Andrographolide from Andrographis paniculata leaf - Mariani Abdul Hamid; Rabe'ah Adam; Faiqah Ramli; Roswanira Wahab (Journal of Tropical Life Science, 2023)
Andrographis paniculata is widely used as a medicinal plant in many countries and andrographolide is the major bioactive compound extracted from A. paniculata leaf. This study purposely to optimize statistical andrographolide extraction using the accelerated solvent extraction (ASE) technique. The Box Behnken design (BBD) was chosen to determine the optimum ASE conditions for the extraction temperature (ºC), cycle number, and extraction time (min) to achieve the highest yield of andrographolide. The optimum ASE conditions were identified as: extraction temperature of 60 ºC, using 3 cycles and 5 min extraction time, with maximum conversion yield as high as 335.2 ± 0.2 mg/g determined by High Performance Liquid Chromatography (HPLC) with the squared correlation coefficients (R2) of 0.97. The findings revealed the ASE method significantly enhanced andrographolide extraction and agreed closely with the predicted value at 337.5 mg/g. Andrographolide was isolated by preparative HPLC technique. A. paniculata leaf extract and extracted andrographolide displayed moderate radical scavenging activity in 2, 2−Diphenyl−1−picrylhydrazyl hydrate (DPPH) assay with IC50 of 0.883 ± 1.597 mg/ml and 0.514 ± 0.285 mg/ml respectively as IC50 for ascorbic acid was 0.048 ± 0.004 mg/ml.  A. paniculata extract and andrographolide inhibited the tyrosinase enzyme with IC50 of 0.749 ± 0.293 μg/ml and IC50 of 2.441 ± 2.026 μg/ml indicated stronger tyrosinase inhibition abilities than kojic acid, IC50 of 19.985 ± 0.557 μg/ml. These results suggest that A. paniculata leaf extract and andrographolide have greater potential as sources of biochemical compounds that can be used as skin depigmentation solutions.